AN IN-DEPTH EXPLORATION INTO RELATIONSHIP OF SOCIAL MEDIA USAGE AND PSYCHOLOGICAL WELL-BEING: AN INSIGHTFUL PERSPECTIVE OF NETWORKING SOCIETY - Uikey, Seema; Parmar, Urvashi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Social media has seamlessly integrated into the lives of individuals, significantly influencing their daily routines. This widespread adoption of social media has led to notable physical and mental repercussions. Research indicates that the usage of social media can notably impact one’s emotional state, with outcomes flowing in both directions. In a recent study, researchers delved into the perceptions of psychologists regarding the intricate interplay between social media utilization and the psychological well-being of its users. The main perspective of the study is to understand the societal changes occurring due to excessive usage of social media. Through structured interviews conducted with five psychologists, the responses were meticulously recorded and analysed. The findings of this investigation underscore that social media undeniably exerts a psychological sway on its users, manifesting as a dual-edged influence encompassing favourable and adverse aspects. This duality hinges upon the nature of the online content individuals are exposed to. The results also reveal that the use of social media prompts individuals to engage in social comparison.